Control engineering and information systems (CRC Press:Balkema, 2015)
Control Engineering and Information Systems contains the papers presented at the 2014 International Conference on Control Engineering and Information Systems (ICCEIS 2014, Yueyang, Hunan, China, 20-22 June 2014).Control Engineering and Information Systems provides a valuable source of information for scholars, researchers and academics in control engineering and information systems.